1987
DOI: 10.1111/j.1528-1157.1987.tb03679.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release Carbamazepine: Cognitive Side Effects in Patients with Epilepsy

Abstract: The treatment of epilepsy with carbamazepine (CBZ) may be hampered by cognitive side effects. These side effects are thought to be related to pharmacokinetic properties of the drug. The serum concentration of CBZ is characterized by rapid absorption and a short half-life, which may lead to a considerable fluctuation of the level between doses. Cognitive defects may result from peak levels: short periods with high serum concentration. In a single-blind crossover design, cognitive performance was compared in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 12 publications
3
32
0
Order By: Relevance
“…Most studies proved extremely poor at detailing the procedure involved; in fact, with the exception of Aman et al ( I 9) and Aldenkamp et al (20), no report addressed or mentioned all of these potentially confounding variables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies proved extremely poor at detailing the procedure involved; in fact, with the exception of Aman et al ( I 9) and Aldenkamp et al (20), no report addressed or mentioned all of these potentially confounding variables.…”
Section: Resultsmentioning
confidence: 99%
“…In view of this, to find small drug effects, we should use the more highly timed measures. Only three of 47 RCTs (19,20,41), however, included automated tests in the cognitive assessment of AEDs.…”
Section: Discussionmentioning
confidence: 99%
“…An example of this is seen with CBZ, which was associated by some workers (9) with negative effects on cognition only during those periods of peak plasma drug concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled-release medication may be most beneficial in memory and visual information processing (Kalvia et al, 1995). Despite these encouraging findings, some investigators suggested that carbamazepine is more likely to lead to cognitive deterioration than improvement (Aldenkamp et al, 1987). Factors that may be related to a greater incidence of cognitive effects include higher dose (Hemsteadter & Witt 2010) longer duration of intake (Shehata et al 2009) and polytherapy (Bourgeosis, 2004).…”
Section: Effect Of Administration Of Carbamazepine And/or Phenytoin Omentioning
confidence: 99%